2008
DOI: 10.1128/aac.00014-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Miltefosine in Old World Cutaneous Leishmaniasis Patients

Abstract: The pharmacokinetics of miltefosine in leishmaniasis patients are, to a great extent, unknown. We examined and characterized the pharmacokinetics of miltefosine in a group of patients with Old World (Leishmania major) cutaneous leishmaniasis. Miltefosine plasma concentrations were determined in samples taken during and up to 5 months after the end of treatment from 31 Dutch military personnel who contracted cutaneous leishmaniasis in Afghanistan and were treated with 150 mg miltefosine/day for 28 days. Samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 28 publications
2
101
2
3
Order By: Relevance
“…Combinations should ideally be matched pharmacokinetically to avoid the exposure of parasites to low concentrations of a single drug. PM, with an elimination half-life of 2.6 h will not optimally protect MF, which has a very long half-life and is still detectable in plasma of patients 5 -6 months after treatment [61]. In contrast, AmBisome has a very long tissue half-life in spleen and liver, and is not prone to the development of resistance.…”
Section: Combination Regimenmentioning
confidence: 97%
See 1 more Smart Citation
“…Combinations should ideally be matched pharmacokinetically to avoid the exposure of parasites to low concentrations of a single drug. PM, with an elimination half-life of 2.6 h will not optimally protect MF, which has a very long half-life and is still detectable in plasma of patients 5 -6 months after treatment [61]. In contrast, AmBisome has a very long tissue half-life in spleen and liver, and is not prone to the development of resistance.…”
Section: Combination Regimenmentioning
confidence: 97%
“…Whilst only demonstrated in three animal models, and whilst two women had apparently normal babies during the Phase IV trial [60], it remains imperative to use prolonged contraception when using MF in women of child-bearing age. Contraception has conventionally been given for 2 -3 months post treatment, but a new finding of a long terminal half-life of over 30 days meant sub-therapeutic concentrations of MF continued to be detected beyond 5 months after treatment [61]. This suggests that contraception should be given for > 3 months, and when this is not feasible, or unlikely to be strictly practiced, MF should be avoided in women of child-bearing age.…”
Section: Mfmentioning
confidence: 99%
“…Since miltefosine as an antileishmanial drug has proven favorable pharmacokinetic profiles in mice 15 and human, 4 the failure of demonstrating in vivo antifungal efficacy in our candidiasis mouse model cannot be attributed to its chemical instability within bloodstream and infection sites. The previous study by Wiederhold et al 14 suggested that protein binding could be associated with the ineffectiveness of miltefosine in the mouse model of disseminated cryptococcosis.…”
mentioning
confidence: 98%
“…3 Pharmacokinetic studies indicate that miltefosine has good bioavailability and a long half-life in patients with leishmania (7 days for the first elimination and 31 days for the terminal elimination). 4 This may be attributable to its improved in vivo antileishmanial activity relative to analogs with even more potent in vitro activities. 3 Miltefosine also possesses antibacterial, 5 antiprotozoal, 6 and antiviral activities.…”
mentioning
confidence: 99%
“…Estudos em ratos tem demonstrado rápido acúmulo do fármaco em rins, fígado, pulmões, baço e outras glândulas. A partir de doses de 30 mg/Kg duas vezes por dia, concentrações de 155 -189 nmol/g de tecido são alcançados (DORLO et al, 2008). A miltefosina é eliminada lentamente, com uma meia-vida de 96 horas (BRESISER et al, 1987).…”
Section: Miltefosinaunclassified